PENGARUH KOMPOS KOTORAN AYAM PADA MEDIA TUMBUH TERHADAP PERTUMBUHAN SEMAI GLODOKAN (Polyalthia longifolia Sonn) - Ridwan, Ridwan; Wardah, Wardah; Wulandari, Retno; Wahyuni, Dewi (Universitas Tadulako, 2020)
Chicken manure compost contains high levels of nitrogen, phosphorus, and potassium nutrients that are useful for plants, the provision of chicken manure compost can improve soil structure on lands that lack on organicmatter. The research was conducted in may-juli 2019 at the palu â€“ poso bpdas permanent seedbed, tadulako university, central Sulawesi. This research used completely randomized design method with four treatments, namely S0 = soil without chicken manure compost; S1 = 1000g of soil : 50g of compost; S2 = 1000g of soil : 100g of compost; S3 = 1000g of soil : 150g of compost. Each treatment was repeated 10 times so that there are a total of 40 experiment units. Growth parameters observed ware seedling height, stem diameter, number of leavers, wet weight, shoot dry weight and seedling root, and seed quality indeks. The results show that chicken manure compost significantly ofected the growth of glodokan seedling growth. Treatment S1 = 1000g of soil : 50g chicken manure compost significantly increases the growth of glodokan seedling, as follows growth of seedling height (5,68 cm), stem diameter (1,44 mm),Â number of leaves (5 leaves), shoot wet weight (2,96 g), root wet weight (0,64g), canopy dry weight (1,19g), root dry weight (0,55g), and seed quality indeks 0,20Kata Kunci: Chicken Manure, Compost, Glodokan, Polyathia longifolia Sonn